2012
DOI: 10.1007/s10464-012-9547-1
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Participation, Gender and Organizational Sense of Community on Psychological Empowerment: The Moderating Effects of Income

Abstract: This study explored the influence of participation, gender and organizational sense of community (SOC) on both the intrapersonal and interactional components of psychological empowerment (PE). Participants were residents (n = 562) involved in community organizing efforts in five U.S. communities. Measures of participation and SOC were tailored to community organization contexts. SOC assessed three dimensions: (1) connection of members to the organization; (2) perceptions about the organization as a bridge to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
98
2
15

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(124 citation statements)
references
References 55 publications
9
98
2
15
Order By: Relevance
“…Some of our findings regarding SOC, however, were not consistent with previous studies. Prior research found SOC to be an important predictor of intrapersonal PE Peterson & Reid, 2003;Speer, Peterson, Armstead, & Allen, 2013). In the present study, participants' SOC was not found to be a unique predictor of intrapersonal PE.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…Some of our findings regarding SOC, however, were not consistent with previous studies. Prior research found SOC to be an important predictor of intrapersonal PE Peterson & Reid, 2003;Speer, Peterson, Armstead, & Allen, 2013). In the present study, participants' SOC was not found to be a unique predictor of intrapersonal PE.…”
Section: Discussioncontrasting
confidence: 60%
“…Several studies have been conducted on the OE model, but tested only certain components (Griffith et al, 2008(Griffith et al, , 2010Hardina, 2011;Ohmer, 2008;Perkins et al, 2007;Speer et al, 2013). The complete model of OE (Peterson & Zimmerman, 2004) remains largely untested and provides an opportunity to test the processes and outcomes within the three components of OE.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, some of the researchers shared same results, indicated contributing factors on participation. It was indicated that participation was influenced by income levels [33]; [37]; [39]; [32]; [38]; [34]; [45]. However, the study did not gather the information of income of the farmers, as respondents were reluctant to share their earnings.…”
Section: Resultsmentioning
confidence: 99%
“…In a study, where the farmers were involved in cleaning of irrigation channels, concluded that the participation level was associated with plot size while the farmers of larger plots were particularly active in water management [32]. Participation positively communicates to intra-personal empowerment across earnings levels, but optimistically related to interactional empowerment only for lowincome individuals [33]. In Nepal, the participation of farmers is influenced by the education level and amount of trainings, while farm size and gross farm income are dominant economic variables influencing participation [34].…”
Section: Introductionmentioning
confidence: 99%